Pengoptimalisasi Potensi Desa Dlingo untuk Meningkatkan Kesejahteraan Masyarakat - Pramusiwi, Aloysia Desy (Jurnal Atma Inovasia, 2022)
KKN is a mandatory activity that is done by the students by providing services for a community, the purpose of this is to apply and actualize every individual student service value in the form of an idea from the knowledge each of them has. KKN is done online, it is also known as KKN Society 5.0, online KKN is being done because of the COVID-19 pandemic that is currently happening. Dlingo Village, Kapanewon Dlingo, Bantul Regency, Special Region of Yogyakarta, is a place that writers want to develop the village’s potential and make pocketbooks related to nature tourism from Dlingo Village. On the first project, discuss about the mapping of Dlingo Village potential from the cultural, natural, and art tourism and also culinary side of things, meanwhile the pocketbook discusses about Dlingo Village natural tourism in a more specific and detailed form. These two projects have a similarity with each other, that similarity is located in the explanation part of the e-book and the pocketbook that in general is a specific explanation that is meant to make the readers realizes Dlingo Village’s potential chronologically and systematically that makes them curious, so that they would eventually visit Dlingo Village.